Real-Time Internet Based Attendance Using Face Recognition System - Wati Mohamad Yusof, Yuslinda; Asyraf Mohd Nasir, Muhammad; Azura Othman, Kama; Izwan Suliman, Saiful; Shahbudin, Shahrani; Mohamad, Roslina (International Journal of Engineering and Technology, 2018)
This project focuses on face recognition implementation in creating fully automated attendance system with a cloud. Cloud services will provide a useful information regarding the attendance such as attendance summary performance and visualizing the data into graph and chart. In this study, we aim to create an online student attendance database, interfaced with a face recognition system based on raspberry pi 3 model B. A graphical user interface (GUI) will provide ease of use for data analysis on the attendance system. This work used open computer vision library and python for face recognition system combined with SFTP to establish connection to an internet server which runs on PHP and Node.js. The results showed that by interfacing a face recognition system with a server, a real-time attendance system can be built and be monitored remotely.Â Â